Pengaruh Persepsi Kemudahan Penggunaan dan Promosi terhadap Minat Penggunaan E-Wallet LinkAja di Kota Surabaya - Muhammad Miftahul Khoir; Ugy Soebiantoro (Universitas Batanghari, 2022)
This journal contributes to understanding the perception of ease of use, promotion and its influence on the interest in using linkaja e-wallets in the city of surabaya. The population in the study are consumers whohave knowledge of linkaja e-wallets as a means of digital payment in the city of surabaya. The use of nonprobability sampling techniques with the accidental sampling method totaled 98 respondents. The quantitative method was chosen with structural equation modeling (sem) data analysis techniques through partial least squares (pls) software. This study obtained findings that the perception of ease of use and joint promotion had a positive effect on the interest in using linkaja e-wallets in the city of surabaya.